صحیح بخاری کی روشنی میں تعلیم و تربیت کے تقاضے اور انسانی نفسیات کا تقابلی مطالعہ: A Comparative Study of Human Psychology and Educational Requirements in the Light of Sahih al-Bukhari - Sana Maryam; Dr Talib Ali Awan (Al Manhal Research Journal, 2025)
This paper examines the role of human psychology in the process of education and training, with a particular focus on the traditions of Sahih al-Bukhari. The study contends that the Prophetic model of teaching, preserved in these authentic narrations, reflects a profound awareness of human nature and is strikingly consistent with the principles of modern educational psychology. Using explanatory and analytical methods, the research explores how the Prophet Muhammad ﷺ employed pedagogical strategies that were sensitive to learners’ psychological states, intellectual capacities, and emotional needs. The analysis highlights five key principles derived from Sahih al-Bukhari: (1) gradualism in the transmission of knowledge, ensuring psychological readiness for change; (2) the use of dialogue and questioning as a means of stimulating active engagement and critical reflection; (3) emphasis on facilitation and ease rather than burdening learners; (4) the method of practical demonstration and role-modeling as an effective tool of instruction; and (5) careful consideration of individual differences in aptitude and capacity. These principles, while rooted in Islamic tradition, correspond closely with contemporary approaches in pedagogy such as learner-centered education, constructivism, and experiential learning. The findings suggest that the Prophetic approach to education was holistic, integrating cognitive, emotional, and moral dimensions of human development. This integration underscores the need for modern Muslim educational systems to revisit the Prophetic model as a source of pedagogical guidance. By aligning Islamic traditions with contemporary educational psychology, a more balanced, humane, and effective framework for teaching and training can be developed, addressing both the spiritual and intellectual growth of learners.